NOVELTIES IN ALYSICARPUS DESV. (FABACEAE) - D. S. POKLE (Research Center for Biology, 1999)
Two new species and two new varieties in the genus Alysicarpus Desv. (Fabaceae) are described. All the new taxa are collected from various parts of Maharashtra. A note on their distribution throughout India is also added.